Face detection and global positioning system on a walking aid for blind people - Abdurrasyid Abdurrasyid; Indrianto Indrianto; Meilia Nur Indah Susanti (Institute of Advanced Engineering and Science, 2022)
Blindness is a general term used for the condition of someone who experiences a disturbance or obstacle in their sense of sight. In general, blind people walk with special canes to help them walk and increase their safety. However, there are problems that arise when blind people walk home or go from a path that they are used to or to a place where they have never traveled. There is the possibility that blind people get lost and find it difficult to determine their way home because they don't know where they are going. For this reason, it is necessary to create a system that can monitor their whereabouts in real time and provide directions, provide information on the steps to their destination and they can also notify their families and related foundations if they are in trouble. For this reason, it is necessary to make an integrated tool with the haar cascade method to detect faces to find out whether there are humans or other obstacles that can shows 94% accuracy, in addition a global positioning system (GPS) can help blind people to show the direction of the destination.